COMPARATIVE STUDY OF THE TRAINING CURRICULUMS OF THE LAW CAREER IN IBERO-AMERICA - Valdivia Bocanegra, María Luisa (2023)
The present investigation has had the purpose of knowing what the main trends in the training of legal professionals at national and international level are, with the purpose of taking them into account, in the curricular updating process, of said program, at the University of San Martín de Porres, in Lima, Peru. The profile of the graduate and the curricular plans have been taken as the study elements. The research is presented as a review article, based mainly on the main academic documents of the analyzed institutions, as well as articles by other authors who have described the situation of lawyer training in different countries. As a main result, it was obtained that, despite having different legal systems as a context, the profiles of the graduates and the study plans are quite like each other. Likewise, the study of Current trends in Law and Law and Technology are appreciated as emerging subjects.